2019
DOI: 10.4314/jae.v23i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Undergraduate Students to Practical Agriculture Experience at the University of Fort Hare, South Africa

Abstract: The study examined perceptions of final year students of agriculture at the University of Fort Hare to practical agricultural experience. A multi-stage sampling procedure was used to obtain data from 278 which were analysed, using descriptive and inferential statistics. The study reveals that more than half (55.0%) had favourable perceptions of practical agriculture experience (PAE). However, only about half (51.1%) expressed a high level of satisfaction. The majority (61.9%) were in favour of on-the-farm inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Only a small percentage of students stated that they were given suitable working tools. Furthermore, few students ( =1.71) acknowledged that they visited farms outside of the university, which contradicts Yusuf et al (2019) findings, which claim that exposing students to commercial farms outside of the university will improve their hands-on experience and expose them to new skills. In total, 72% of students favored PYP, while 28% did not.…”
Section: Analysis Of the Perspectives Of Pyp By Thementioning
confidence: 78%
See 2 more Smart Citations
“…Only a small percentage of students stated that they were given suitable working tools. Furthermore, few students ( =1.71) acknowledged that they visited farms outside of the university, which contradicts Yusuf et al (2019) findings, which claim that exposing students to commercial farms outside of the university will improve their hands-on experience and expose them to new skills. In total, 72% of students favored PYP, while 28% did not.…”
Section: Analysis Of the Perspectives Of Pyp By Thementioning
confidence: 78%
“…According to Subbiah, Kannan, Koiyu, and Monama (2017), industrial training was relevant and provided students with the essential skills to meet job market needs. Yusuf et al (2019) found that more than half of the respondents in a South African study had favorable perceptions of practical farm experience. However, in the study of Karunaratne and Perera (2019), despite the fact that students' perceptions of the internship programme were positive, with the claim that they were exposed to learning experiences and the opportunity to develop a relationship with the industry, acquire industry work culture, develop self-confidence, execute problem-solving activities, develop social interaction skill, and aspire future education and career, the students negatively ranked the internship programme in providing opportunities to develop social interaction skills and aspire future education and career.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation